2008
DOI: 10.1590/s0102-37722008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento e barreiras

Abstract: RESUMO -Este estudo analisa as barreiras percebidas à prática de atividade física e os estágios de mudança de comportamento de idosos institucionalizados preservados cognitivamente. Trinta participantes responderam ao Mini-Exame do Estado Mental, ao Questionário sobre Estágios de Mudança de Comportamento e ao Questionário sobre Barreiras à Prática de Atividade Física. Os resultados mostraram que poucos idosos institucionalizados apresentam uma alta percepção de descrença nos benefícios da atividade física. Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
1
1
0
9
Order By: Relevance
“…The results of this study showed that individuals aged ≥ 60 years had greater tendency to perceive health problems as a reason preventing or discouraging them from engaging in leisure-time physical activity compared with individuals aged < 60 years. In a study with 30 Brazilian institutionalized elderly, Gobbi et al 27 noted that health-related barriers were the most common, while lack of time was less perceived, mirroring the results of the present study for this age group. The authors of this study held that for elderly, lack of time is less frequently perceived because this group has very few activities to occupy them in their daily routines.The need for rest and lower ability appear to be health-related factors influencing the perception of elderly, given that in this age group individuals tend to feel more tired and have less physical and motor ability to perform certain activities, which may lead to the perception that they lack the health conditions to engage in physical activity.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study showed that individuals aged ≥ 60 years had greater tendency to perceive health problems as a reason preventing or discouraging them from engaging in leisure-time physical activity compared with individuals aged < 60 years. In a study with 30 Brazilian institutionalized elderly, Gobbi et al 27 noted that health-related barriers were the most common, while lack of time was less perceived, mirroring the results of the present study for this age group. The authors of this study held that for elderly, lack of time is less frequently perceived because this group has very few activities to occupy them in their daily routines.The need for rest and lower ability appear to be health-related factors influencing the perception of elderly, given that in this age group individuals tend to feel more tired and have less physical and motor ability to perform certain activities, which may lead to the perception that they lack the health conditions to engage in physical activity.…”
Section: Discussionsupporting
confidence: 87%
“…Dos 95 que remanesceram no processo e foram encaminhados para avaliação pelos seus textos integrais, foram excluídos 82, tendo como principais motivos: amostra não continha a faixa etária de interesse (n = 30) e ausência da análise de barreiras para a prática de AF (n = 19). Dessa forma, 13 artigos originais responderam adequadamente aos critérios de inclusão e compuseram a síntese descritiva [14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Resultsunclassified
“…Em relação aos objetivos, as pesquisas propuseram--se desde a identificação mais geral das barreiras para as AF 14,16,18,21,23,24,26 às questões mais específicas, relacionadas à dor 20 , e à manutenção e/ou desistência de programas de AF 15,25 . Apenas o artigo de Gobbi et al 19 buscou identificar e analisar as barreiras associadas à inatividade física.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…These results corroborate the study conducted by Brazão et al, (20) who observed that 50.5% of the elderly patients in the sample did not practice and had no interest in physical activity over the next 6 months (pre-contemplation) and a small portion did not practice physical activity, but planned to practice in the near future (contemplation and preparation). In another study, conducted with institutionalized elderly patients, it was found that 76% of individuals presented inactive behavior, and, of these, 56% were in the pre-contemplation stage, followed by contemplation and preparation stages (21) . The process of health behavior change requires strategies and activities that aim at advancing the patient to the next stage.…”
Section: Discussionmentioning
confidence: 95%